Profiling of drug crystallization in the skin. (1st September 2020) - Goh, Choon Fu; Boyd, Ben J.; Craig, Duncan Q. M.; Lane, Majella E.
ABSTRACT: Background: Drug crystallization following application of transdermal and topical formulations may potentially compromise the delivery of drugs to the skin. This phenomenon was found to be limited to the superficial layers of the stratum corneum ( 7 µm) in our recent reports and tape stripping of the skin samples was necessary. It remains a significant challenge to profile drug crystallization in situ without damaging the skin samples. Methods: This work reports the application of an X-ray microbeam via synchrotron SAXS/WAXS analysis to monitor drug crystallization in the skin, especially in the deeper skin layers. Confocal Raman spectroscopy (CRS) was employed to examine drug distribution in the skin to complement the detection of drug crystallization using SAXS/WAXS analysis. Results: Following application of saturated drug solutions (ibuprofen, diclofenac acid, and salts), CRS depth profiles confirmed that the drugs generally were delivered to a depth of 15 – 20 µm in the skin. This was compared with the WAXS profiles that measured drug crystal diffraction at a depth of up to 25 µm of the skin. Conclusion: This study demonstrates the potential of synchrotron SAXS/WAXS analysis for profiling of drug crystallization in situ in the deeper skin layers without pre-treatment for the skin samples.